HCN Regulates Cellular Processes through Posttranslational Modification of Proteins by S-cyanylation - García, Irene (Plant Physiol, 2019)
Hydrogen cyanide (HCN) is coproduced with ethylene in plant cells and is primarily enzymatically detoxified by the mitochondrial β-CYANOALANINE SYNTHASE (CAS-C1). Permanent or transient depletion of CAS-C1 activity in Arabidopsis (Arabidopsis thaliana) results in physiological alterations in the plant that suggest that HCN acts as a gasotransmitter molecule. Label-free quantitative proteomic analysis of mitochondrially enriched samples isolated from the wild type and cas-c1 mutant revealed significant changes in protein content, identifying 451 proteins that are absent or less abundant in cas-c1 and 353 proteins that are only present or more abundant in cas-c1. Gene ontology classification of these proteins identified proteomic changes that explain the root hairless phenotype and the altered immune response observed in the cas-c1 mutant. The mechanism of action of cyanide as a signaling molecule was addressed using two proteomic approaches aimed at identifying the S-cyanylation of Cys as a posttranslational modification of proteins. Both the 2-imino-thiazolidine chemical method and the direct untargeted analysis of proteins using liquid chromatography-tandem mass spectrometry identified a set of 163 proteins susceptible to S-cyanylation that included SEDOHEPTULOSE 1,7-BISPHOSPHATASE (SBPase), the PEPTIDYL-PROLYL CIS-TRANS ISOMERASE 20-3 (CYP20-3), and ENOLASE2 (ENO2). In vitro analysis of these enzymes showed that S-cyanylation of SBPase Cys(74), CYP20-3 Cys(259), and ENO2 Cys(346) residues affected their enzymatic activity. Gene Ontology classification and protein-protein interaction cluster analysis showed that S-cyanylation is involved in the regulation of primary metabolic pathways, such as glycolysis, and the Calvin and S-adenosyl-Met cycles.